Study on nutrient status of aonla orchard soils in Sikar district of Rajasthan (Indian Journal of Arid Horticulture, 2025)
Studies were conducted on the mineral nutrition status of aonla fruit orchards located in Sikar district of Rjasthan. Electrical conductivity was found to be in normal range and soil pH was in the high ranging from 7.70 to 9.18. The organic carbon content and available nitrogen of aonla orchard soils were found low whereas available phosphorus, available iron, zinc, copper, and manganese were found low to medium. Available potassium was found medium whereas available sulphur was found low in range. The soils were found medium to high in exchangeable Ca and Mg. There was wide variation found in the calcium carbonate percentage at different soil depths in orchards.
Keywords: aonla; Anonymous; magnitude; scanty